The Development of Android and Web-based Logical Thinking Measurement Tools as an Alternative Solution for Research Instruments - Rahman, Abdul; Usman, Mulbar; Ahmar, Ansari Saleh (Journal of physics. Conference series, 2018)
This type of research is a development research or it is known by the term of Research and Development (R & D). The focus of this research is to develop a logical reasoning ability measurement tool based on qualified Web and Android as a research instrument alternative solution. The implementation of this research is conducted on Statistics Department in the Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar. The subject of the study in question is the students of Statistics Department of Universitas Negeri Makassar. Measurement tool that will be developed is a Test of Logical Thinking (TOLT). The development of this information system using PHP programming language based on CodeIgniter Framework with MySQL database.